2009
DOI: 10.4049/jimmunol.0803684
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Colitogenic CD4+ Memory T Cells Residing Outside the Intestine Participate in the Perpetuation of Chronic Colitis

Abstract: To understand the perpetuation of inflammatory bowel disease (IBD), it is important to clarify whether the colitogenic CD4+ T cells are self-limited effector or long-lived memory T cells. We here investigate the latency of colitogenic CD4+ T cells in the remission stage of colitis under germfree (GF) conditions. We isolated splenic (SP) CD4+ T cells from colitic CD4+CD45RBhigh T cell-injected SCID mice maintained under specific pathogen-free (SPF) conditions and transferred them into SPF or GF SCID mice. Donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…In the colon, the commensal bacteria are approximately 100-fold denser than in the SI [14]. Consistently, germ-free rag-2 −/− transferred with CD4 + CD45RB high T cells did not develop colitis and ileitis [15], suggesting that colitis is dominantly mediated along with commensal bacteria, while ileitis may be dependent on other factors.…”
Section: Discussionmentioning
confidence: 89%
“…In the colon, the commensal bacteria are approximately 100-fold denser than in the SI [14]. Consistently, germ-free rag-2 −/− transferred with CD4 + CD45RB high T cells did not develop colitis and ileitis [15], suggesting that colitis is dominantly mediated along with commensal bacteria, while ileitis may be dependent on other factors.…”
Section: Discussionmentioning
confidence: 89%
“…Because the spleen and lymph nodes are dispensable for the development of chronic colitis,13 we found that BM is the main source of IL-7 14 15. We previously demonstrated that, in addition to a major subpopulation of T EM cells, a substantial proportion of colitogenic CD4 central memory cells preferentially reside in the BM of colitic mice 16 17. Importantly, these resident BM CD4 memory T cells are closely associated with IL-7-producing stromal cells and retain a significant potential to induce colitis after adoptive retransfer into new SCID/RAG-2 –/– mice.…”
Section: Introductionmentioning
confidence: 94%
“…T H 1 and T H 17 cells have both been implicated in the pathogenesis of the disease. In experimental models of IBD circulating colitogenic memory CD4 T cells required the presence of gut commensals to induce inflammation and IBD pathogenesis (86). In mouse models of IBD transfer experiments of gut CD4 TRM transferred disease to RAG2 −/− mice (87).…”
Section: Trm In Chronic Inflammatory Diseasesmentioning
confidence: 99%